Pengaruh Stres Kerja dan Beban Kerja Terhadap Turnover Intention Karyawan Pada PT Panasonic Manufacturing Indonesia - Basrun, Lusy Yuniar; Agung, Syahrum; Kuraesin, Ecin (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2023)
This study aims to determine the effect of work stress, workload on employee turnover intention. This research method is quantitative, and the population used is employees of PT Panasonic Manufacturing Indonesia with a sample size of 50 respondents to Business Unit X employees. Researchers used data collection techniques in the form of observation, questionnaires, literature study. The instrument test results in this study used multiple regression analysis, t test, and then f test and the results obtained from this study are that on the Job Stress variable (X1), positive and significant results are obtained for the employee turnover intention variable (Y), which can be interpreted as having high work stress for employees, so will high turnover intention. the workload variable (X2) has a positive and significant relationship to employee turnover intention, which means that there is a high workload, the higher the turnover intention.